The relationship between personality factors, vocational identity and career decision-making self-efficacy - Emanuel Sebastian Turda (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Context: Adolescence is the training ground for adult life. In a relatively short period, the adolescent will undergo a metamorphosis. During the high school years, the majority of adolescents move from persistent dependence to true independence, from logical thinking to abstract, complex and hypothetical thinking, from impulsivity to consideration and from a diffuse feeling about one's own person to a reasonably defined self-identity. Adolescent's vocational identity formation during high school is an extremely important process in vocational and career counseling, because it helps them to make rational choices regarding the choice of a career gaining an increased level of career maturity. Methods: The present study had as participants 300 Romanian teenagers which belong to the following paths of studies/profiles: formal sciences (specializations: Mathematics-informatics and Natural Sciences), services (specializations: Economics, trade, tourism and food) and humanities (specialization: Philology). The tools used in the adolescent evaluation process were Career Decision-Making Self-Efficacy-Short Form Scale (CDMSE-SF), the Vocational Identity Status Assessment (VISA) and the NEO Five-Factor Inventory (NEO-FFI-3). Results: After the interpretation of the obtained results, the following aspects were demonstrated: The identity status career commitment correlates with the personality traits - neuroticism, extraversion, openness to experience and conscientiousness, and regarding the career decision-making self-efficacy it correlates with the self-evaluation process, obtaining information about self and professions, setting goals, career planning and the problem-solving process. Identity status identification with career commitment correlates with personality traits - extraversion, openness to experience and conscientiousness, and from the perspective of the career decision-making self-efficacy, it correlates with the process of self-evaluation, obtaining information about self and professions, setting goals, solving problems and career planning. The identity status career commitment flexibility correlates with the personality traits neuroticism and conscientiousness, and from the perspective of the career decision-making self-efficacy it correlates with the problem-solving process. Identity status career self-doubt correlates positively with the personality trait neuroticism and negatively with conscientiousness, the process of self-evaluation, obtaining information about self and professions, setting goals, career planning and problem solving. Conclusion: The main purpose of this study was to investigate the relationship between vocational identity, personality factors and career decision-making self-efficacy. The results demonstrated that certain personality traits, respectively certain components of career decision-making self-efficacy are predictors for the adolescent's vocational identity formation.
Keywords: 330; Adolescents; Career Decision-Making Self-Efficacy; Personality Factors; Predictors; VET; Vocational Education and Training; Vocational Identity